Barriers and facilitators to implementation of non-medical independent prescribing in primary care in the UK: a qualitative systematic review - Nicola Carey; Judith Edwards; Melaine Coward (BMJ Open)
Objectives To support workforce deficits and rising demand for medicines, independent prescribing (IP) by nurses, pharmacists and allied health professionals is a key component of workforce transformation in UK healthcare. This systematic review of qualitative research studies used a thematic synthesis approach to explore stakeholders’ views on IP in primary care and identify barriers and facilitators influencing implementation.Setting UK primary/community care.Participants Inclusion criteria were UK qualitative studies of any design, published in the English language. Six electronic databases were searched between January 2010 and September 2021, supplemented by reference list searching. Papers were screened, selected and quality-appraised using the Quality Assessment Tool for Studies with Diverse Designs. Study data were extracted to a bespoke table and two reviewers used NVivo software to code study findings. An inductive thematic synthesis was undertaken to identify descriptive themes and interpret these into higher order analytical themes. The Diffusion of Innovations and Consolidated Framework for Implementation Research were guiding theoretical anchors.Primary and secondary outcome measures N/A.Results Twenty-three articles addressing nurse, pharmacist and physiotherapist IP were included. Synthesis identified barriers and facilitators in four key stages of implementation: (1) ‘Preparation’, (2) ‘Training’, (3) ‘Transition’ and 4) ‘Sustainment’. Enhancement, substitution and role-specific implementation models reflected three main ways that the IP role was used in primary care.Conclusions In order to address global deficits, there is increasing need to optimise use of IP capability. Although the number of independent prescribers continues to grow, numerous barriers to implementation persist. A more coordinated and targeted approach is key to overcoming barriers identified in the four stages of implementation and would help ensure that IP is recognised as an effective approach to help alleviate workforce shortfalls in the UK, and around the world.PROSPERO registration number CRD42019124400.